2010
DOI: 10.1175/2009jpo4330.1
|View full text |Cite
|
Sign up to set email alerts
|

Wavenumber Spectrum in the Gulf Stream from Shipboard ADCP Observations and Comparison with Altimetry Measurements

Abstract: The wavenumber spectra for velocity and temperature in the Gulf Stream region are calculated from a decade (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) of shipboard acoustic Doppler current profiler (ADCP) measurements taken as part of the Oleander Project. The velocity and temperature spectra have comparable magnitude, in terms of the kinetic and potential energy, and both indicate a k -3 slope. These results are in agreement with twodimensional quasigeostrophic turbulence theory. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 16 publications
(12 reference statements)
6
76
0
Order By: Relevance
“…That discussion (e.g. Stammer, 1997;Le Traon et al, 2008;Wang et al, 2010), however, has largely ignored the internal-wave field emphasized in earlier works (e.g. Katz, 1973).…”
Section: Theoretical Predictions For Submesoscale Wavenumber Spectramentioning
confidence: 97%
See 2 more Smart Citations
“…That discussion (e.g. Stammer, 1997;Le Traon et al, 2008;Wang et al, 2010), however, has largely ignored the internal-wave field emphasized in earlier works (e.g. Katz, 1973).…”
Section: Theoretical Predictions For Submesoscale Wavenumber Spectramentioning
confidence: 97%
“…The potential energy spectra were instead reported to scale close to P k ∼ k −2 in both mixed layer and thermocline. Wang et al (2010) analyzed a long-term data set of mixed-layer velocities and temperatures in the Gulf Stream region, along a transect between New York Harbor and Bermuda. They found that the energy spectra fall off approximately like K k ∼ P k ∼ k −3 on scales between 250 km and 20 km, consistent with interior QG turbulence.…”
Section: Mixed-layer Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra are based on the Discrete Fourier Transform (DFT) determined from the Fast Fourier Transform (FFT) (see Sch16 or Wang et al [15], who also used the DFT to analyze TEX spectra). The FFT requires equally spaced, gap-free data, i.e., gaps, if they exist in the original series, must be filled and the data must be interpolated to equal spacing, if not already equally spaced, prior to applying the FFT algorithm.…”
Section: The Spectral Approachmentioning
confidence: 99%
“…Although the constant interior PV assumption seems to be too strong [La- Is has also been argued that the SQG may be a better framework for the upper ocean balanced dynamics since the slope of (along-track) altimeter-derived SSH wavenumber spectra at mesoscales seem to be more consistent with the slope predicted by SQG turbulence theory [e.g., Le Traon et al, 2008] than with the slope predicted by the classical QG turbulence theory and previously used to rationalize SSH observations [e.g., Stammer, 1997]. However, altimeter-derived spectra slopes do not seem to match those few estimates from in-situ observations [Wang et al, 2010], likely owing to noise contamination in altimeter measurements even at mesoscales [e.g., Fu, 2011, 2012].…”
Section: Introductionmentioning
confidence: 84%